TEACHING REPORT TEXT BY USING SCIENTIFIC APPROACH WITH DISCOVERY LEARNING STRATEGIES - Abdullah Azzam Akbar; Ahmad Syafi'i; Haris Dibdyaningsih (Journal of English Language Teaching and Islamic Integration, 2024)
A newly designed curriculum called as K-13 (Curriculum 2013) was officially implemented in the beginning of 2013. A scientific approach becomes the most significant part of it. Some researchers had researched about implementation of scientific approach in theclassroom and they found that the implementation is not optimal. There are many teachers who are not able to implement scientific approach perfectly, the teachers use less than five steps that actually must be implemented in the classroom. Most of teachers had difficulty in implementing scientific approach because they have a little knowledge about it.